The transferability of lipid loci across African, Asian and European cohorts - Karoline Kuchenbaecker (Nature Portfolio, 2019)
The majority of published GWAS was performed in European ancestry populations. Here, Kuchenbaecker et al., test to which extent lipid loci are shared and find that the major lipid loci are mostly transferrable between Europeans and Asians while there are notable exceptions for African populations.